The Relation Between Social Anxiety and Audience Perception: Examining Clark and Wells' (1995) Model Among Adolescents. Issue 5 (September 2014) - Blöte, Anke W.; Miers, Anne C.; Heyne, David A.; Clark, David M.; Westenberg, P. Michiel
<x content-type="archive" xml:space="preserve">Abstract</x> Background: Clark and Wells' cognitive model of social anxiety proposes that socially anxious individuals have negative expectations of performance prior to a social event, focus their attention predominantly on themselves and on their negative self-evaluations during an event, and use this negative self-processing to infer that other people are judging them harshly. Aims: The present study tested these propositions. Method: The study used a community sample of 161 adolescents aged 14–18 years. The participants gave a speech in front of a pre-recorded audience acting neutrally, and participants were aware that the projected audience was pre-recorded. Results: As expected, participants with higher levels of social anxiety had more negative performance expectations, higher self-focused attention, and more negative perceptions of the audience. Negative performance expectations and self-focused attention were found to mediate the relationship between social anxiety and audience perception. Conclusions: The findings support Clark and Wells' cognitive model of social anxiety, which poses that socially anxious individuals have distorted perceptions of the responses of other people because their perceptions are coloured by their negative thoughts and feelings.